Mutation patterns of 16 genes in primary and secondary acute myeloid leukemia (AML) with normal cytogenetics - Fernandez-Mercado, M; Yip, B; Pellagatti, A; Davies, C; Larrayoz, M; Kondo, T; Pérez, C; Killick, S; McDonald, E; Odero, MD; Agirre, X; Prósper, F; et al. (Public Library of Science, 2012)
Acute myeloid leukemia patients with normal cytogenetics (CN-AML) account for almost half of AML cases. We aimed to study the frequency and relationship of a wide range of genes previously reported as mutated in AML (ASXL1, NPM1, FLT3, TET2, IDH1/2, RUNX1, DNMT3A, NRAS, JAK2, WT1, CBL, SF3B1, TP53, KRAS and MPL) in a series of 84 CN-AML cases. The most frequently mutated genes in primary cases were NPM1 (60.8%) and FLT3 (50.0%), and in secondary cases ASXL1 (48.5%) and TET2 (30.3%). We showed that 85% of CN-AML patients have mutations in at least one of ASXL1, NPM1, FLT3, TET2, IDH1/2 and/or RUNX1. Serial samples from 19 MDS/CMML cases that progressed to AML were analyzed for ASXL1/TET2/IDH1/2 mutations; seventeen cases presented mutations of at least one of these genes. However, there was no consistent pattern in mutation acquisition during disease progression. This report concerns the analysis of the largest number of gene mutations in CN-AML studied to date, and provides insight into the mutational profile of CN-AML.